A study on top management commitment and ISO 9000 certification - Tan, Chin Keng (2010)
The research aims to determine the level of top management commitment towards quality management and whether there is significant difference on top management commitment towards quality management implementation between construction organizations with and without ISO 9000 certification. The research methodology of questionnaire survey is applied in data collection for the research, the data is analysed with the descriptive statistics and hypothesis testing. Research findings indicate that the top management of a construction organization is generally committed to the implementation of quality management from perspectives of quality goals, efforts, involvement, attitude to change and resources allocation. However, it is also found that the top management does not place quality as the priority against the factor of cost and time. In addition, there is not conclusive finding indicating difference on top management commitment towards quality management implementation between ISO 9000 certified and non-ISO 9000 certified organizations.